LEGITIMACY OF IMMEDIATE EXECUTABLE JUDGMENT (UITVOERBAAR BIJ VOORRAAD) IN SMALL CLAIMS COURT - Gerry Geovant Supranata Kaban; Afifah Kusumadara; Dhia Al Uyun (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The immediate executable judgment (uitvoerbaar bij voorraad) is a form of judgment in civil procedural law that can be executed first, even though it does not yet have permanent legal force (inkracht van gewijsde). In the context of small claims court, the issuance of an immediate executable judgment raises questions regarding its legitimacy and implications for the principles of justice and legal certainty. This research aims to analyze the legitimacy of issuing immediate executable judgment in small claims court cases through juridical aspects. The research method used is normative juridical with a normative legal research approach and a conceptual approach. The data used includes relevant legal regulations, court decisions, and relevant legal literature. The research results indicate that judges have the authority and legitimate legitimacy to issue immediate executable judgment when examining, adjudicating, and deciding small claims court cases while still adhering to the strict terms and conditions outlined in Article 180 paragraph (1) of the HIR and Article 191 paragraph (1) of the RBg junctis SEMA Number 3 of 2000 concerning Immediate Executable Judgment (Uitvoerbaar bij Voorraad) and Provisional, to ensure aspects of legal certainty, usefulness, and justice.